Feral pigeons in urban environments: Dietary flexibility and enzymatic digestion? - Ciminari, María Eugenia (2005)
Columba livia, original from Europe, is at present widely distributed all over the world. These granivores colonized urban environments where the availability of crops and seeds is not always permanent and, for that are forced to exploit other resources with different composition, e.g. high protein foodstuff. Thus, feral pigeons should have the ability to survive on a diet rich in protein as they do with starchy items by having an adequate digestive biochemical machinery to process it. Phylogenetical and functional hypothesis has been proposed linking dietary flexibility and enzyme lability. All Passeriformes studied to date show the expected positive correlation between aminopeptidase-N and dietary protein but not for intestinal carbohydrases. Conversely, all the non-passerine species modulate intestinal carbohydrases, but not peptidases. Moreover, different scenarios may be posed as the output of a phylogenetical effect, e.g., adding constraints to a lability scheme in certain groups or just determining it (e.g., intestinal disaccharidases modulated in Galloanserae and peptidases modulated in Passeriformes). Consequently, we tested the prediction that feral pigeons adjust digestive enzyme activities according to the level of the respective substrate (e.g., carbohydrates, protein) in the diet. Birds were fed for 15 days with two different diets, one with high protein content (low in starch) (HP) and the other rich in starch and low in proteins (HS). Pigeons fed on the HP were able to survive with no other dietary supplement, as predicted. Pancreatic enzymes did not change between diet treatments. Birds fed on HP exhibited the predicted upward modulation of aminopeptidase-N activity, when compared to birds on HS, while intestinal carbohydrases did not show differences between diets. These results give an apparent support to the functional hypothesis, but are not enough to reject that the observed intestinal protease lability has a phylogenetical component, because feral pigeons are closely related to Passeriformes. Finally, feral pigeons have the ability to take full advantage of the energy content from proteins, having enough pancreatic proteases activity and modulating the intestinal aminopeptidase-N. These abilities may allow them to use effectively the nutrients found in the cities surviving even when grains are not available along the year.